Angina Relief by Ranolazine Identifies False-Negative SPECT Myocardial Perfusion Scans in Patients with Coronary Disease Demonstrated by Coronary Angiography - Murray, Gary L. (International Journal of Angiology, 2014)
Normal myocardial perfusion imaging (MPI) reduces intermediate- or high-risk pretest probability patients to low- or intermediate-risk posttest probability, respectively, for coronary disease (CD). Since ranolazine (RAN) relieves only angina, anginal patients with normal MPI whose angina is relieved by RAN present a significant dilemma. The purpose of this retrospective chart review was to confirm the impression that coronary angiography (CA) is indicated in patients whose class 3 to 4 angina is relieved by RAN, but have normal myocardial single-photon emission computed tomography (SPECT) MPIs. Charts of patients with stable class 3 to 4 angina (typical and atypical) and normal MPIs (left ventricular ejection fraction [LVEF] ≥50% and segmental score = 0) were reviewed. CA was done on all the patients with complete angina relief taking RAN, as well as nonresponders whose anginal etiology could not be explained. Stenoses were considered flow-restrictive when more than 70% diameter stenosis is observed by quantitative CA, or, when 50 to 70%, fractional flow reserve (FFR) measured ≤0.80. RAN relieved angina in 36 of 54 (67%) patients. Of the known cases, 25 of these 36 (69%) had 43 stenoses ≥50% (mean = 66%): 15 (60%) had 1 vessel disease; 9 (36%) had multivessel disease; 18 (72%) had left anterior descending (LAD) disease; 1 (4%) had left main disease. Twenty one of 43 (49%) stenosis were > 70%; 22 (51%) stenoses were 50 to 70% and required FFR measurement. Twenty nine of 43 stenoses (67%) were considered flow-restrictive in 18 of these 25 (72%) patients. Eight RAN nonresponders with no explanation for angina had no CD at CA. RAN angina relief is invaluable in identifying falsely negative SPECT MPI, and 50% of these patients have flow-restrictive stenoses.
Keywords: ranolazine; coronary disease; angina; myocardial SPECT perfusion; cardiac catheterization; fractional flow reserve